Relationship between obesity and musculoskeletal disorders: systematic review and meta-analysis (Research, Society and Development, 2021)
Introduction: Obesity is considered a public health problem and it is associated with various musculoskeletal disorders, that haven´t been reviewed systematically. Therefore, the objective of this study was to describe the relationship between these changes in individuals with obesity. Methods: Lilacs, PubMed, Scielo, Scopus and Web of Science electronic databases were systematically reviewed until July 2018, conducted according to Cochrane guidelines for the development of meta-analysis. Eligibility criteria: inclusion (studies with humans; with a BMI greater than 30 Kg/m² or above the 85th and 95th percentile for children and adolescents; articles published in Portuguese, English, and Spanish; articles with validated evaluation methods); exclusion (duplicate, non-indexed articles; special populations; meeting summaries, editorials, letters to the editor and reviews). Results: Based on moderate evidence, knee postural changes in patients with obesity were found in two studies (n=158) (OR 14,26, IC 95% 4,98-40,80), I2 = 0% (p = 0,000), foot postural changes were found in 3 studies (n =338) (OR 3,20, IC 95% 2,08-4,94), I2=0% (p=0,000). Two studies were identified for arthritis (n=1331) (OR 3,38, IC 95% 0,72-1582), I2=38,95% (p=0,122). Pain was reported in the lower limb and the spine. Four studies were found for the former (n=1560) (OR 5,51 IC 95% 2,07-14,61), I2=81,02% (p=0,001), and three for the latter (n=499) (OR 9,78 IC 95% 2,59-36,93), I2=86,58% (p=0,000). Conclusion: Results show that obesity has a negative impact on musculoskeletal health, with results statistically significant for knee and foot postural changes, arthritis, and pain in the spine and lower limbs.